University-Publisher Relationship Revisited – ‘Policy Statement by Academic Libraries on the Pricing of Scholarly Journals’ - Roosendaal, Hans E. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
The consortium of Dutch universities, the Dutch Royal Library and the Netherlands Institute for Scientific Information have summer 1999 developed and implemented a new strategy in its relationship to scientific publishing houses.